2022
DOI: 10.5114/wiitm.2022.120960
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus laparoscopic right colectomy for colon cancer: a systematic review and meta-analysis.

Abstract: The aim of the study was to compare the short-term surgical outcomes of robotic right colectomy (RRC) with laparoscopic right colectomy (LRC) for colon cancer, to evaluate the safety and feasibility of the robotic surgery system. Material and methods: A systematic literature review was conducted using the PubMed, Web of Science, Embase, and Cochrane Library databases regarding the comparison of RRC vs. LRC for colon cancer in the last 5 years. Studies were included as per the PICOS criteria, and relevant event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The operative time for laparoscopic surgery was significantly shorter than that for robotic surgery, due to subjective factors that might implicate the learning curve, the experience of the surgeon, but also the complexity of the case and because of the time needed for each instrument change [44,45]. This finding corroborates the work of previous meta-analyses that suggested efficiency in operative time as a key advantage of laparoscopic surgery [46]. It is pertinent to consider that extended operative times associated with robotic surgery may not reflect inefficiency but also encompass the learning curve for surgeons less experienced with robotic techniques.…”
Section: Discussionsupporting
confidence: 85%
“…The operative time for laparoscopic surgery was significantly shorter than that for robotic surgery, due to subjective factors that might implicate the learning curve, the experience of the surgeon, but also the complexity of the case and because of the time needed for each instrument change [44,45]. This finding corroborates the work of previous meta-analyses that suggested efficiency in operative time as a key advantage of laparoscopic surgery [46]. It is pertinent to consider that extended operative times associated with robotic surgery may not reflect inefficiency but also encompass the learning curve for surgeons less experienced with robotic techniques.…”
Section: Discussionsupporting
confidence: 85%
“…The study concluded that RRC had lower conversion rates (P = 0.03), shorter duration of hospitalization (P = 0.01), but longer operative time (P < 0.001), compared to LRC. Moreover, comparable outcomes were observed between the two techniques regarding blood loss, lymph node retrieval, and overall complications [21].…”
Section: Literature Reviewmentioning
confidence: 68%
“…124 Meta-analyses generally support the findings seen in retrospective reviews and database studies. 125,126 Overall, RC is associated with shorter LOS, lower conversion rate, higher number of LN examined, and longer operative time, without impact on overall morbidity or mortality compared to LC.…”
Section: Colon Cancermentioning
confidence: 98%